An Integrative Sialomic Analysis Reveals Molecules From Triatoma sordida (Hemiptera: Reduviidae) - Praça, Yanna Reis; Santiago, Paula Beatriz; Charneau, Sébastien; Mandacaru, Samuel Coelho; Bastos, Izabela Marques Dourado; Bentes, Kaio Luís da Silva; Silva, Sofia Marcelino Martins; da Silva, Waldeyr Mendes Cordeiro; da Silva, Ionizete Garcia; de Sousa, Marcelo Valle; Soares, Célia Maria de Almeida; Ribeiro, José Marcos Chaves; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Triatomines have evolved salivary glands that produce versatile molecules with various biological functions, including those leading their interactions with vertebrate hosts’ hemostatic and immunological systems. Here, using high-throughput transcriptomics and proteomics, we report the first sialome study on the synanthropic triatomine Triatoma sordida. As a result, 57,645,372 reads were assembled into 26,670 coding sequences (CDS). From these, a total of 16,683 were successfully annotated. The sialotranscriptomic profile shows Lipocalin as the most abundant protein family within putative secreted transcripts. Trialysins and Kazal-type protease inhibitors have high transcript levels followed by ubiquitous protein families and enzyme classes. Interestingly, abundant trialysin and Kazal-type members are highlighted in this triatomine sialotranscriptome. Furthermore, we identified 132 proteins in T. sordida salivary gland soluble extract through LC-MS/MS spectrometry. Lipocalins, Hemiptera specific families, CRISP/Antigen-5 and Kazal-type protein inhibitors proteins were identified. Our study provides a comprehensive description of the transcript and protein compositions of the salivary glands of T. sordida. It significantly enhances the information in the Triatominae sialome databanks reported so far, improving the understanding of the vector’s biology, the hematophagous behaviour, and the Triatominae subfamily’s evolution.